Effort to Prevent the Radicalism among Students through the Establishment of Religious Values in the Concept of State Defense at Universitas Islam Kadiri - Jatmiko, Udik (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.35, 2020)
the purposed is to give information about the radicalism avoidance process, give the view of religious values instruction and establishment in the concept of state defense in college students of Universitas Islam Kadiri (Uniska) Kediri. The subject of this research is the first semester students of each study program in Uniska, lecturer of Bela Negara (state defense) subject, and lecturers of Islamic religion subject. This research uses descriptive qualitative design, supported by primary data including interview result, observation, and documentation. The result of research shows that the effort of radicalism avoidance process through religious values instruction and establishment in the concept of state defense has been implemented in Uniska continuously, either in the academic through Bela Negara lesson or non-academic through religious activity which includes Islamic and nationalism insight based. Those efforts, at least, are able to reduce radicalism actions by showing tolerance education, especially implementing the democratic education concept and reasoning construction through religious and nationalist values in college students, especially by giving the understanding about pluralism, nationalism, human right enforcement, fairness, democratic goodness and gender equality in doing the good thing in the college area of society.